Анализ влияния оплаты труда на деятельность коммунального комплекса региона - Лукьянец А. А.; Ротарь В. Г. Виктор Григорьевич; Шумский А. А.; Ерофеев Е. Л.; Чернов А. Г. (2005, 2005)
В фонде НТБ ТПУ отсутствует